Study On Harmful Effects Of Opium On Liver And Lungs In Chronic Opium Addicts Of Western Rajasthan - Pawan, M; Choudhary, Raghuveer; Mathur, Ranjana; Choudhary, MR; Kamla, M (Journal of Bangladesh Society of Physiologist, 2012)
Background: Today opium dependence is widely prevalent in certain states of India, especially Rajasthan, Punjab, Haryana, Madhya Pradesh (MP) etc. In rural areas of western Rajasthan crude opium is consumed with a social acceptance by a notable proportion (8.0%) of adult male population. Later on they become addicted to it. Objective: to observe the changes in some liver and lung function parameters in opium addicted subjects of Barmer city of Western Rajasthan. Methods: The present study was conducted in district hospital of Barmer, Rajasthan. Total fifty (50) adult male subjects with age ranged from 30 to 50 years were participated in this study. Among them 25 were opium addicted and were considered as study group (Group B) and another 25 apparently healthy adult male of same age group were designated as control group (Group A). Opium addicts were consuming about 5–11 gm/day opium for >2 years. Then liver function tests were evaluated by estimating serum aspartate amino transferase (AST), alanine amino transferase (ALT), alkaline phosphatase and lung function tests by measuring FVC, FEV1 , FEV1/FVC% , PEF, FEF 25-75% of both the groups. Results: In this study AST, ALT and alkaline phosphatase levels were found significantly (p<.05) higher in group B as compared to those of group A. Again, FVC, FEV1, FEV1/ FVC were significantly (p<.05) lower in group B as compared to those of group A. PEF (L/sec) and FEF 25-75% were also significantly (p<0.001) lower in group B as compared to those of group A. Conclusion: it is concluded that chronic long term use of opium, increases the risk of hepatic and pulmonary damage. DOI: http://dx.doi.org/10.3329/jbsp.v6i2.9762 JBSP 2011 6(2): 122-126